Macroeconomic risk and growth in the Southeast Asian countries : insight from SEA - Barnett, William A.; Sergi, Bruno S. (Emerald Publishing Limited, 2023)
ASEAN economies have much insight to offer the world, from investor behaviour during COVID-19, and deep-rooted attitudes towards risk and corruption, to achievement of the Sustainable Development Goals through the gender perspective. The authors examine complex and pressing issues, including: competing models of risk reporting, the effect of corporate governance on the Indonesian stock market, and the influence of stakeholders in influencing the level of disruptive innovation disclosure in 15 countries around the world. ISETE-33B gives fresh insight into financial and economic issues in ASEAN countries, written by authors from diverse backgrounds. This is essential reading for anyone interested in the financial evolution of these fast-moving economies.
Includes index.
Keywords: Economics -- Southeast Asia.; Macroeconomics.; ASEAN.; Business & Economics -- Economics -- Macroeconomics.; elektronické knihy; electronic books